PARP inhibitor resistance in breast and gynecological cancer: Resistance mechanisms and combination therapy strategies - Wang, Nannan; Yang, Yan; Jin, Dongdong; Zhang, Zhenan; Shen, Ke; Yang, Jing; Chen, Huanhuan; Zhao, Xinyue; Yang, Li; Lu, Huaiwu (Frontiers in Pharmacology, 2022)
Breast cancer and gynecological tumors seriously endanger women's physical and mental health, fertility, and quality of life. Due to standardized surgical treatment, chemotherapy, and radiotherapy, the prognosis and overall survival of cancer patients have improved compared to earlier, but the management of advanced disease still faces great challenges. Recently, poly (ADP-ribose) polymerase (PARP) inhibitors (PARPis) have been clinically approved for breast and gynecological cancer patients, significantly improving their quality of life, especially of patients with BRCA1/2 mutations. However, drug resistance faced by PARPi therapy has hindered its clinical promotion. Therefore, developing new drug strategies to resensitize cancers affecting women to PARPi therapy is the direction of our future research. Currently, the effects of PARPi in combination with other drugs to overcome drug resistance are being studied. In this article, we review the mechanisms of PARPi resistance and summarize the current combination of clinical trials that can improve its resistance, with a view to identify the best clinical treatment to save the lives of patients.